Examining the Hierarchical Influences of the Big-Five Dimensions and Anxiety Sensitivity on Anxiety Symptoms in Children - Wauthia, Erika; Lefebvre, Laurent; Huet, Kathy; Blekic, Wivine; El Bouragui, Khira; Rossignol, Mandy (Frontiers in Psychology, 2019)
Anxiety sensitivity (AS), namely the fear of anxiety symptoms, has been described as a precursor of sub-threshold anxiety levels. Sexton and colleagues (2003) posited that increased AS would arise from an elevated neuroticism and that both would act as vulnerability factors for panic disorder (PD), obsessive-compulsive disorder (OCD) and generalized anxiety disorder (GAD) symptoms. Accordingly, this study aimed to (1) evaluate the applicability of this model to a pediatric population and (2) examine the influences of the other Big-Five personality dimensions on the four lower-order dimensions of AS (cognitive, physical, control and physical) and on social phobia (SP), separation anxiety disorder (SAD) and depression symptoms. 200 children (104 girls) aged between 8 and 12 years old (mean age=132.52 months, SD = 14.5) completed the Childhood Anxiety Sensitivity Index (Silverman et al., 1991), the Big Five Questionnaire for Children (Barbaranelli et al., 2003) and the Revised’s Children Anxiety and Depression Scale (Chorpita et al., 2000). Regression analyses confirmed that AS and neuroticism together significantly predicted the presence of PD, OCD and GAD symptoms but also social phobia (SP), separation anxiety disorder (SAD) and depression symptoms. Moreover, neuroticism interacted with extraversion, conscientiousness and agreeableness to significantly predict SP, GAD and depression. Surprisingly, global AS score was only predicted by agreeableness while AS dimensions also specifically related to openness. Finally, AS dimensions did not predict the presence of specific anxiety symptoms. To conclude, the predicting model of anxiety symptoms in children set neuroticism and AS on the same level, with an unexpected influence of agreeableness on AS, raising the importance of other trait-like factors in the definition of such models. Moreover, AS should be considered as a unitary construct when predicting the presence of anxiety symptoms in children. Future interventions 56 must take into account these associations to help children to detect and recognize their 57 symptoms of anxiety and help them to interpret them correctly.